Mapping the collaborative research process - Kochanek, Julie Reed; Scholz, Carrie; Garcia, Alicia J (Education Policy Analysis Archives, 2015)
Despite significant federal investments in the production of high-quality education research, the direct use of that research in policy and practice is not evident. Some education researchers are increasingly employing collaborative research models that use structures and processes to integrate practitioners into the research process in an effort to produce more relevant and useful work. This article presents and describes the logic model developed by researchers at American Institutes for Research (AIR) to guide their work on the Regional Educational Laboratory Midwest. Under this program, AIR researchers have developed eight research alliances. The alliance members, who represent districts, state education agencies, and other organizations with a vested interest in education, partner with researchers to develop three- to five-year research agendas. These agendas drive the research and technical assistance projects that the alliance members and AIR researchers do together. It contributes to the emergent literature on research-practice partnerships, providing a theory-based approach to the work that others might model, build upon, or revisit.